Tiga Kerajaan Besar Islam: Safawi, Mughal, dan Turki Usmani - Mukhtar Amiruddin Ahmad; Mujiburrahman Mujiburrahman (Jurnal Pengetahuan Sosial dan Sejarah, 2026)
This study analyzes the social, political, economic, and intellectual dynamics of the pre-modern period of the Islamic world by focusing on three major empires: the Safavid in Persia, the Mughal in India, and the Ottoman in Anatolia. This period was marked by both the zenith of Islamic civilization and the onset of significant decline. The Safavid Empire, under Shah Ismail and reaching its golden age during the reign of Shah Abbas I, established Twelver Shi‘ism as the state religion, implemented centralized bureaucracy, expanded international trade, and promoted advancements in art, architecture, and philosophy. The Mughal dynasty, particularly under Akbar through Aurangzeb, consolidated political stability, developed agricultural and export-based trade systems, and produced monumental legal works such as Fatawa Alamgiri as well as architectural masterpieces like the Taj Mahal. In contrast, the Ottoman Empire began to experience military defeats and administrative weakness, which spurred an awareness of the need for reform through diplomacy and the adoption of Western technology, though often hindered by resistance from the ulema and Janissary corps. Overall, this period reflects the transition of the Islamic world from global supremacy toward stagnation and a reactive stance toward Western modernity, eventually laying the groundwork for the Islamic reform movements of the 18th and 19th centuries.